Penguatan Layanan Primer untuk Ketahanan Jaminan Kesehatan Nasional dalam Perspektif Islam: Studi Kasus di PKU Kotagede Yogyakarta - Mohammad Jailani (Jurnal Kesehatan Islam : Islamic Health Journal, 2024)
Abstract This study analyzes the strengthening of primary healthcare services to support the resilience of the National Health Insurance (JKN) from an Islamic perspective through a case study at PKU Muhammadiyah Kotagede Hospital, Yogyakarta. This research's primary focus is applying Islamic principles such as justice, compassion, and social responsibility in managing primary healthcare services. The methodology is qualitative, utilizing in-depth interviews, field observations, and document analysis for data collection. The findings reveal that integrating Islamic values in healthcare services at PKU Kotagede enhances accessibility and service quality while supporting JKN resilience by reducing the burden on secondary services and improving cost efficiency. This research contributes to the health literature by demonstrating how a religion-based approach can strengthen national health systems and offers practical recommendations for developing other healthcare services grounded in religious values in Indonesia. Keywords: Strengthening primary healthcare, healthcare services, national health, Islamic studies